2021
DOI: 10.3171/2021.2.focus201098
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of tumor-related potential spinal column instability (Spine Instability Neoplastic Scores 7–12) eventually requiring surgery with a 1-year follow-up

Abstract: OBJECTIVE Within the Spine Instability Neoplastic Score (SINS) classification, tumor-related potential spinal instability (SINS 7–12) may not have a clear treatment approach. The authors aimed to examine the proportion of patients in this indeterminate zone who later required surgical stabilization after initial nonoperative management. By studying this patient population, they sought to determine if a clear SINS cutoff existed whereby the spine is potentially unstable due to a lesion and would be more likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been reported that more than 50% of patients with ≥ 10 points of SINS underwent stabilization and only 11% of patients with ≤ 9 points underwent instrumented fusion [ 20 ]. Moreover, Vargas et al reported that patients with SINS of greater than 10 had increased surgery rates with a 1-year follow-up [ 21 ]. On the other hand, regarding radiation therapy, patients with higher SINS (median 10 points of SINS), and with spinal metastases, had increased rates of radiation failure [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 50% of patients with ≥ 10 points of SINS underwent stabilization and only 11% of patients with ≤ 9 points underwent instrumented fusion [ 20 ]. Moreover, Vargas et al reported that patients with SINS of greater than 10 had increased surgery rates with a 1-year follow-up [ 21 ]. On the other hand, regarding radiation therapy, patients with higher SINS (median 10 points of SINS), and with spinal metastases, had increased rates of radiation failure [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these reports, it has been possible to define a cutoff where the spine is considered possibly unstable and would be more likely to require stabilization. This is the case of patients with SINS score of 11 or greater (45).…”
Section: What About Scores Ranging Between 7 and 12mentioning
confidence: 99%